MTR3D: identifying regions within protein tertiary structures under purifying selection. Issue Volume 49:Issue W1(2021) (29th May 2021) - Silk, Michael; Pires, Douglas E V; Rodrigues, Carlos H M; D'Souza, Elston N; Olshansky, Moshe; Thorne, Natalie; Ascher, David B
Abstract: The identification of disease-causal variants is non-trivial. By mapping population variation from over 448, 000 exome and genome sequences to over 81, 000 experimental structures and homology models of the human proteome, we have calculated both regional intolerance to missense variation (Missense Tolerance Ratio, MTR), using a sliding window of 21–41 codons, and introduce a new 3D spatial intolerance to missense variation score (3D Missense Tolerance Ratio, MTR3D), using spheres of 5–8 Å. We show that the MTR3D is less biased by regions with limited data and more accurately identifies regions under purifying selection than estimates relying on the sequence alone. Intolerant regions were highly enriched for both ClinVar pathogenic and COSMIC somatic missense variants (Mann–Whitney U test P < 2.2 × 10 −16 ). Further, we combine sequence- and spatial-based scores to generate a consensus score, MTRX, which distinguishes pathogenic from benign variants more accurately than either score separately (AUC = 0.85). The MTR3D server enables easy visualisation of population variation, MTR, MTR3D and MTRX scores across the entire gene and protein structure for >17, 000 human genes and >42, 000 alternative alternate transcripts, including both Ensembl and RefSeq transcripts. MTR3D is freely available by user-friendly web-interface and API at http://biosig.unimelb.edu.au/mtr3d/ . Graphical Abstract: